ASSESSING MUTILITERACY AMONG HIGH SCHOOL STUDENTS: A COMPREHENSIVE STUDY - Dwina, Lasma (SEAQIL Journal of Language Education, 2025)
Indonesia curriculum indicates that the nature of literacy in Indonesia has expanded beyond the traditional domains of language instruction (Listening, Speaking, Reading, and Writing) to encompass multimodal communication, with a focus on strengthening students' critical viewing and presenting skills. This study aims to contribute to this growing area of research by assessing the level of digital literacy skills among senior high school students. Using the analytical framework, this qualitative case study illuminates how students engaged in multiliteracy pedagogy from receptive skills to productive skills. In total, 210 students of second grade participated, of which 100% living in city area. Data include classroom observations, semi-structured interviews with students, and digital work. Results of digital work analyses showed the average level of literacy skills among teenagers in urban area is at low level. However, data also showed that students experienced meaningful practice of multiliteracy and critical thinking. Students experienced four dimensions of multiliteracy pedagogy and improved their critical thinking. Time is the key to reconcile prior experiences and common conceptions of language and language learning with the sophisticated, scientific definition of literacy that leads to the challenge of bringing the many facets and tenets of literacy together into a conceptual whole. Researcher suggests that EFL teachers find ways for learners to become multiliterate communicators with learning experiences of multiliteracy in English classes.